Determination of Plant Hormones in Fertilizers by High-Performance Liquid Chromatography with Photodiode Array Detection: Method Development and Single-Laboratory Validation - Gambino, Grazia Laura; Pagano, Pietro; Scordino, Monica; Sabatino, Leonardo; Scollo, Emanuele; Traulo, Pasqualino; Gagliano, Giacomo (Journal of AOAC International, 2008)
A simple and reliable high-performance liquid chromatographic method that uses photodiode array detection was developed for the simultaneous determination of 12 native and synthetic plant hormones, i.e., plant growth regulators (PGRs), in fertilizers, such as 1-naphthol, 2,4-dichlorophenoxyacetic acid, 4-(2,4-dichlorophenoxy)butyric acid, 4-chlorophenoxyacetic acid, indole-3-acetic acid, 4-(3-indolyl)butyric acid, dichlorprop, (4-chloro-2-methylphenoxy)acetic acid, α-naphthaleneacetic acid, 1-naphthaleneacetamide, β-naphthoxyacetic acid, and thidiazuron. The method was experimentally validated for routine regulatory application, and the following analytical parameters were assessed for all PGRs studied: linearity; specificity; precision (relative standard deviation) and accuracy, both measured at 3 concentration levels (0.1, 0.05, and 0.01%, w/w); ruggedness; limit of detection; and limit of quantification. Results were satisfactory for all method validation parameters tested and for all PGRs studied, demonstrating the suitability of the method for the determination of PGRs in fertilizers. The uncertainty of measurement was also estimated at 3 concentration levels for all PGRs by using the approach of the International Organization for Standardization, described in its Guide to the Expression of Uncertainty in Measurement. The method was applied to 20 samples of liquid fertilizer with declared biostimulant properties.